"Exploring this whole thing of social justice" narrative as a tool for critical sociocultural knowledge development in teacher education. (2nd January 2019) - Vlach, Saba Khan; Taylor, Laura; Mosley Wetzel, Melissa
ABSTRACT: Many teacher education programs provide teachers with opportunities to read, write, and discuss critical pedagogy, with the hope that such work will allow them to develop more equitable and just teaching practices. Yet, there often remains a gap between the theoretical discussions of teaching and learning in teacher education classrooms and the pedagogical practice in those teachers' K-12 classrooms. In this study, we examine how one teacher, Gabriela, used narratives to make connections between her third-grade classroom and the critical concepts she was exploring in a teacher education course. Embedded within an ethnographic case study of an inservice teacher education program, we used a discourse analytic approach to examine both the sociocultural knowledge and the identities Gabriela constructed through narrative as she engaged with issues of language, race, and power within the course. We consider some of the affordances of narrative in this space, including how it allowed Gabriela to integrate her understandings of multiple course topics, to position herself in multiple ways as a teacher, and to disrupt her existing understandings of race and racism in the classroom. This analysis suggests that critically oriented teacher education programs might more intentionally make space for narrative to connect critical theory and pedagogical practice.